Perspektif Ibnu Khaldun tentang Sejarah Pendidikan Islam di Indonesia - Noormawanti, Noormawanti (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2021)
In the explanation of the history of Islamic education in Indonesia in terms of Ibn Kholdun's philosophy of history, it can be concluded that the history of the philosophy of history has a strong relationship with Islamic education, because Ibn Kholdum's philosophy was incorporated in the study of expedition theory in the past, which had the same vision of seeking validation. Although specifically Ibn Khaldun is more concerned with the issue of science than the Brothers of Shafa, but in other contexts in general terms that Ibn Khaldun has thoughts that are not much different from the Ikhwan Safa. the thought of Ibn Khaldun who said that the effort to get a true knowledge is to take a natural process that has been possessed by every human being through the capture of the five senses.